Conventional and unconventional reversible logic gates on Physarum polycephalum. Issue 2 (4th March 2017) - Schumann, Andrew
Abstract : In this paper, we consider different ways of designing reversible logic gates on Physarum polycephalum motions using controlling stimuli such as attractants and repellents. Repellents are needed because of uncertainty in the direction of plasmodium propagation to eliminate some directions as unimportant. In this way, we can construct conventional reversible logic gates: the CNOT gate, the FREDKIN gate, the TOFFOLI gate, etc. Combinations of reversible logic gates are regarded as matrix multiplications. Nevertheless, the plasmodium in its networking can permanently change its decisions and without repellents we have an extension of matrix multiplication group theory. Within this extension we can design unconventional reversible logic gates, where the number of inputs and outputs is uncertain.